Centro Histórico de Belém: lugar de história e memória na sala de aula - MARTINS, Lourdes Machado (Universidade Federal do Pará, 2019)
The dissertation Centro histórico de Belém: place of history and memory in the classroom, aims to develop a didactic proposition, to teach history from heritage sources, incorporating the use of local historical patrimony. The experiment was carried out at the State School of Elementary and Middle School Rui Barbosa, located at Rua Joaquim Távora, 408 in the neighborhood of Cidade Velha. For this research, two monuments of the Historic Center of Belém were selected: the Castle Fort and the Frei Caetano Brandão Square, as a space for the development of teaching and learning in interface with local history. The result was considered positive, because a great involvement of the students with the proposed tasks was observed, a fact that favored the learning of the same ones. As an educational product of the dissertation, the third chapter presents the pari passu of the didactic preposition that proposes to be used in teaching history in different series and levels of teaching. The didactics of history used foresees a methodological course in which the teacher will be the interlocutor in dialogue with the students, because it is he who will present to the students the sources that will be used, as well as, guide them in the construction of reflections about the historical patrimony , whose main objective is to stimulate the construction of historical knowledge in different spaces of memory. The students, in turn, will be agents of this research, since they will have the opportunity to analyze the sources directly and, at different times, they will be the interlocutors through the answers that they will find in the crossing of the sources to each presented question, whose objective is to approach the students of local history through direct contact with sources and local themes. The project was theoretically reflected in the debates and disciplines in the first group of the Professional Master's Degree in History Teaching, highlighting the Rüsenian didactics in epistemological interaction with the debates about heritage education. The study of the historical center from the perspective of heritage education is the educational product as a result of the master's thesis that seeks to make the dialogue between epistemology and praxis.